Contingencies of intellectual capitals and financial capital on value creation. Issue 1 (12th January 2015) - Tseng, Kuo-An; Lin, Ching-I; Yen, Szu-Wei
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the relationship among intellectual capital (IC), financial capital (FC), firm value (V), and value creation (VC) in different business cycles (BC) for the conduct of strategic management that will maintain stable values and further increase V. Design/methodology/approach – This research cites ICs as "other information" to combine ICs and the Ohlson model. Information provided by various capitals is validated by multiple regression analysis. Multi-group analysis is performed to test whether the coefficient is moderated by BC. Findings – Results indicate the significant information of ICs and FC, and the contingency perspective of BC. The value relevance of ICs is moderated by BC. Prosperity has more explanatory capacities, and recession ICs yield more incremental information. Research limitations/implications – VC is influenced by both ICs and FC. Besides, the macroeconomic situation should also be considered in strategic management and VC management. Practical implications – In addition to ICs and FC, the macroeconomic situation must be taken into account when conducting strategic management, valuation management, investment decision, or industrial policy. Social implications – Results indicate a contingency of BC, which can be a reference for enterprises to create higher V, for investors to make appropriate investment, as well as for governments to formulate sound industrial policies. Originality/value – This paper applies BC to explore the value relevance of ICs and FC, leverages two models to represent V and VC, and cites complete four aspects of IC as "other information" to combine ICs and Ohlson model.